The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1189/jlb.0410222
|View full text |Cite
|
Sign up to set email alerts
|

Cytohesin-1 regulates fMLF-mediated activation and functions of the β2 integrin Mac-1 in human neutrophils

Abstract: The nucleotide exchange factor cytohesin-1 was previously reported to interact with the cytoplasmic domains of the integrin β-chain common to all β(2) integrins such as LFA-1 and Mac-1. We show here that cytohesin-1, which contributes to fMLF-induced functional responses in PMNs through activation of Arf6, restrains the activation of the β(2) integrin Mac-1 (αMβ(2)) in PMNs or dcAMP-differentiated PLB-985 cells. We found that the cytohesin-1 inhibitor SecinH3 or siRNA increased cell adhesion to immobilized fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 72 publications
3
31
0
Order By: Relevance
“…The following conclusions were obtained:

A clear hierarchy of measured parameters was obtained: spreading could not be normal if durable arrest frequency was normal, and durable arrest could no be stimulated in patients’ cells if total arrests were lacking.

As expected, Mn ++ -induced arrests were normal in patients cells, validating the possibility of detecting individual interactions provided integrin unbending was correctly induced.

Total arrest frequency was normal, but durable arrest frequency was decreased in fMLF-stimulated neutrophils, confirming the importance of active cell functions to stabilize arrests in contrast with short-term molecular interactions (Pierres et al, 1994). This is consistent with the hypothesis that the integrin extension induced by fMLF (Diamond and Springer, 1993; El Azreq et al, 2011) might be obtained in absence of kindlin-3. It was not feasible to ascribe the arrest stabilization and spreading defects to incomplete integrin activation or defect of fMLF-induced clustering (Detmers et al, 1987).

…”
Section: Leukocyte Adhesion Deficiency Type III Exemplifies the Consesupporting
confidence: 91%
“…The following conclusions were obtained:

A clear hierarchy of measured parameters was obtained: spreading could not be normal if durable arrest frequency was normal, and durable arrest could no be stimulated in patients’ cells if total arrests were lacking.

As expected, Mn ++ -induced arrests were normal in patients cells, validating the possibility of detecting individual interactions provided integrin unbending was correctly induced.

Total arrest frequency was normal, but durable arrest frequency was decreased in fMLF-stimulated neutrophils, confirming the importance of active cell functions to stabilize arrests in contrast with short-term molecular interactions (Pierres et al, 1994). This is consistent with the hypothesis that the integrin extension induced by fMLF (Diamond and Springer, 1993; El Azreq et al, 2011) might be obtained in absence of kindlin-3. It was not feasible to ascribe the arrest stabilization and spreading defects to incomplete integrin activation or defect of fMLF-induced clustering (Detmers et al, 1987).

…”
Section: Leukocyte Adhesion Deficiency Type III Exemplifies the Consesupporting
confidence: 91%
“…19 Further studies have extended the role of cytohesins in regulating integrin functions to other cell types such as neutrophils and dendritic cells, and the precise adhesion-mediating effect of CYTH1 has been found to be highly context and cell-type dependent. [26][27][28] Our findings now extend the role of CYTH1 to HSPCs in addition to mature blood cells.…”
Section: Discussionsupporting
confidence: 64%
“…Notably, the authors demonstrated that either amplification of ErbB2 or increased levels of the ErbB3/ErbB4 ligand heregulin led to de novo or acquired cetuximab resistance (18), and Ruan et al achieved similar results in a breast cancer study (19). Cytohesins, family members of GTPases, have been researched for their regulation of the reassembly of the cytoskeleton and the activation of integrin or the integrin signaling system, which is critically associated with cell adhesion and migration (11,20,21). A further study identified that cytohesins as EGFR activators may form a layer of positive regulation by facilitating the structural rearrangements required to convert the receptor dimer into its active conformation in lung cancer (10).…”
Section: Discussionmentioning
confidence: 99%